2021
DOI: 10.1007/s10143-021-01665-4
|View full text |Cite
|
Sign up to set email alerts
|

Development and assessment of machine learning models for predicting recurrence risk after endovascular treatment in patients with intracranial aneurysms

Abstract: Intracranial aneurysms (IAs) remains a major public health concern and endovascular treatment (EVT) has become a major tool for managing IAs. However, the recurrence rate of IAs after EVT is relatively high, which may lead to the risk for aneurysm re-rupture and re-bleed. Thus, we aimed to develop and assess prediction models based on machine learning (ML) algorithms to predict recurrence risk among patients with IAs after EVT in 6 months. Patient population included patients with IAs after EVT between January… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Notable contributions include Tanioka et al ’s creation of an AI model for predicting delayed cerebral ischemia ( 40 ), Kim et al ’s development of an AI-explainable predictive model for vasospasm prediction ( 41 ), and Bizjak et al ’s model to predict the growth of untreated IAs based on baseline aneurysm morphology ( 42 ). Additionally, some potential sub-fields, such as recurrence prediction for IAs after treatment ( 43 ) and effectiveness prediction after endovascular treatment ( 44 ), remain underexplored and warrant further investigation in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Notable contributions include Tanioka et al ’s creation of an AI model for predicting delayed cerebral ischemia ( 40 ), Kim et al ’s development of an AI-explainable predictive model for vasospasm prediction ( 41 ), and Bizjak et al ’s model to predict the growth of untreated IAs based on baseline aneurysm morphology ( 42 ). Additionally, some potential sub-fields, such as recurrence prediction for IAs after treatment ( 43 ) and effectiveness prediction after endovascular treatment ( 44 ), remain underexplored and warrant further investigation in the future.…”
Section: Discussionmentioning
confidence: 99%
“…D max has been demonstrated to have predictive value for ruptured aneurysms, and the rupture status can independently predict aneurysm recurrence. Based on clinical experience, neurosurgeons tend to regard IAs with a larger N as being associated with a high risk of recurrence ( 15 ). However, there have been limited studies regarding the significance of N in multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Current models for predicting aneurysm recurrence are limited. Lin et al explored the short-term recurrence model in 6 months based on significant variables in the univariate analysis ( 15 ). We developed a novel predictive model based on independent risk factors, with an average follow-up of 12.53 months.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has demonstrated the growing application of ML models in the medical sector [11][12][13][14][15][16].ML models incorporate a variety of advanced algorithms to handle different data characteristics, including State-Action-Reward-State-Action , Random Forest Classi er, Deep Q Network, and Support Vector Machine [17].In comparison to traditional regression models, ML has been validated as an effective method for prognosis prediction in modeling due to its capacity to intricately analyze complex non-linear interrelations among variables [18,19], and to enhance prediction accuracy through its superior algorithms, particularly when analyzing large datasets with numerous variables [20,21]. Crucially, the widespread adoption of Electronic Patient Record systems and the extensive use of structured patient data have made sophisticated algorithmic modeling and bedside application feasible [22].…”
Section: Introductionmentioning
confidence: 99%